Crack detection in welded joint - Abdul Mutalib Faisal, Lampong (University Malaysia Sarawak, UNIMAS., 2005)
In this experimental study on specimen of mild steel pipe, non destructive testing method of ultrasonic will be used base on acoutoelastic. Four specimen of mild steel pipe were used; not welded, half welded and two fully welded. Each specimen was then tested by using panametric, Epoch III flaw detector.